Broadband nonlinear behaviour of a soft magneto-sensitive elastomer cantilever under low-frequency and low-magnitude excitation. (September 2018) - Yang, Zhaoshu; Tang, Lihua; Xie, Mengying; Sun, Shuaishuai; Li, Weihua; Aw, Kean
In this article, a soft magneto-sensitive elastomer cantilever with strong nonlinear behaviour is presented. With the help of a permanent magnet, a strong nonlinear behaviour is observed under low-frequency and low-magnitude excitation, which demonstrated its potential for vibrational energy harvesting. A theoretical model is developed which incorporates the nonlinear magnetic interaction in an Euler–Bernoulli beam. The theoretical model is further discretized using finite element method, and the frequency response was obtained through numerical simulation. Frequency sweep experiment was conducted to validate the model and investigate the nonlinear behaviour of the cantilever under different excitations. With the validated model, various contributing factors were parametrically studied to investigate their influences towards the dynamic behaviour of the cantilever. The results show that magnetic force dominates the linear stiffness increase of soft magneto-sensitive elastomer cantilever rather than the magnetorheological effect, and the nonlinear performance of soft magneto-sensitive elastomer cantilever mainly derives from horizontal magnetic force variations during vibration. These properties make the soft magneto-sensitive elastomer cantilever an attractive candidate to automatically tune and broaden the operational bandwidth of vibrational energy harvesters.